A SIMULTANEOUS COUPLING AZO-DYE METHOD FOR THE QUANTITATIVE ASSAY OF ESTERASES: BIOCHEMICAL CHARACTERIZATION (Iraqi Journal of Medical Sciences, 2016)
Background:Enzyme activity is a subject of continuous research. Comparison of data obtained from various quantitative methods needs standardization of techniques in order to verify the results of histochemical and biochemical assays utilized in the study of tissue enzyme activity.Objective:Establishment of a biochemical method for the quantification of enzyme activity in ?-naphthyl acetate esterases (ANAE) containing solution using hexazotized pararoseaniline (HP) as a coupling agent.Methods:Wavelength of maximum absorbance (?max) of coupled HP in solution was analyzed spectrophotometrically based on the simultaneous-coupling method of ANAE demonstration.Results:?max of the coupled HP was found to be at 425 nm. The relationship between the optical density of the final reaction product (FRP) and the enzyme concentration was linear with the use of azo dye in solution.Conclusion:Data obtained from the biochemical assay of ANAE activity was in agreement with those documented by the histochemical methods in use. Thus, characterization of enzyme activity may be standardized when studying tissue sections and tissue homogenates.Keywords: Esterases, Biochemical assay, Histochemistry, Spectrophotometry
Keywords: Esterases; Biochemical assay; Histochemistry; Spectrophotometry